Effects and Moderators of Acute Aerobic Exercise on Subsequent Interference Control: A Systematic Review and Meta-Analysis - Oberste, Max; Javelle, Florian; Sharma, Sophia; Joisten, Niklas; Walzik, David; Bloch, Wilhelm; Zimmer, Philipp (Frontiers in Psychology, 2019)
Background: Acute aerobic exercise leads to positive physiological adaptations within the central nervous system. These findings inspired research on potential cognitive benefits following acute aerobic exercise. The effects of acute aerobic exercise on subsequent cognitive performance, by far, have been the most researched for interference control, a subcomponent of executive function. The results of primary studies on the effects of acute aerobic exercise on subsequent interference control performance are inconsistent. Therefore, we used meta-analytic methods to pool available effect sizes, and to identify covariates that determine the magnitude of exercise-induced interference control benefits. Methods: Medline, PsycINFO, and SPORTDiscus were searched for eligible records. Hedges' g corrected standardized mean difference values (SMDs) were used for analyses. Random-effects weights were used to pool effect sizes. Moderator analyses were conducted using meta-regressions and subgroups analyses. Covariates that were here tested for moderation included parameters of the applied exercise regimen (exercise intensity and exercise duration), characteristics of examined participants (age and fitness), and methodological features of existing research (type of control group, familiarization with test procedure, type of test variable, delay between exercise cessation, and testing). Results: Fifty studies, with data from 2,366 participants, were included in qualitative and quantitative synthesis. A small, significant beneficial effect of acute aerobic exercise on time-dependent measures of interference control was revealed (k = 49, Hedges' g = −0.26, 95%CI: −34 to −0.18). Effect sizes from time-dependent measures of interference control varied widely and heterogeneity reached statistical significance (T2 = 0.0557, I2 = 28.8%). Moderator analyses revealed that higher exercise intensities (vigorous intensity and high-intensity interval training), also participants at younger or older age, and participants who are familiar with the testing procedure prior to the experiment, benefitted most from acute aerobic exercise. However, noticeable heterogeneity remained unexplained within specific subgroups (high-intensity interval training, preadolescent children, and active and supervised control group). Conclusion: Acute aerobic exercise improves subsequent interference control performance. However, the covariates exercise intensity, participants' age, and familiarization with testing procedure determine the magnitude of that effect. Methodological features were not found to influence the magnitude of effects. This dismisses some doubts that exercise induced benefits for interference control performance are scientific artifacts. The fact that large heterogeneity remained unexplained in some subgroups indicates the need for further research on covariates within these subgroups. It should be noted that effect sizes for all analyses were small.